Safe Communities for Sustainable Development: Smart Policing in Local Communities in Slovenia - Lobnikar, Branko; Prislan Mihelič, Kaja (10. Nacionalna konferenca o varnosti v lokalnih skupnostih: Mirna, varna in inkluzivna družba ter varnost v lokalnih skupnostih, 2024)
Ensuring security and resilience in sustainable development is increasingly connected with developing smart and safe communities. Municipalities have a significant (co)responsibility for ensuring safety and fostering smart and sustainable development by promoting various initiatives for community safety and residents' quality of life. This article presents a study conducted among representatives of Slovenian municipalities regarding developing smart and safe communities in Slovenia. We assessed the maturity of smart community components, how municipalities perceive the benefits and challenges of this development, and the projects implemented in the area of safe communities. The education and healthcare sectors were identified as the most developed. Mobility, energy, and agriculture were ranked lowest in priority, while security remains underdeveloped. Municipalities emphasize the principles of inclusion, connectivity, and collaboration, with safety projects focusing on traffic solutions, public space management, and information services. The main challenges of smart community development are municipalities' limited competencies and infrastructure capacities.